Step
*
of Lemma
coSet-equality2
∀x,y:coSet{i:l}.
  ((∀T:𝕌'. ((((a:Type × (a ⟶ T)) ⊆r T) ∧ (coSet{i:l} ⊆r T)) 
⇒ (x = y ∈ T) 
⇒ (x = y ∈ (a:Type × (a ⟶ T)))))
  
⇒ (x = y ∈ coSet{i:l}))
BY
{ RepeatFor 2 (Intro) }
1
1. x : coSet{i:l}
2. y : coSet{i:l}
⊢ (∀T:𝕌'. ((((a:Type × (a ⟶ T)) ⊆r T) ∧ (coSet{i:l} ⊆r T)) 
⇒ (x = y ∈ T) 
⇒ (x = y ∈ (a:Type × (a ⟶ T)))))
⇒ (x = y ∈ coSet{i:l})
Latex:
Latex:
\mforall{}x,y:coSet\{i:l\}.
    ((\mforall{}T:\mBbbU{}'.  ((((a:Type  \mtimes{}  (a  {}\mrightarrow{}  T))  \msubseteq{}r  T)  \mwedge{}  (coSet\{i:l\}  \msubseteq{}r  T))  {}\mRightarrow{}  (x  =  y)  {}\mRightarrow{}  (x  =  y)))  {}\mRightarrow{}  (x  =  y))
By
Latex:
RepeatFor  2  (Intro)
Home
Index